Findings about the feminization of social work. Santa Fe in the 40 years (Papeles, 2023)
This article is prepared within the framework of a degree research for the Bachelor of Social Work. The theme is the Feminization of Social Work, in the context of the professionalization process in Santa Fe in the 40s. The findings made so far are shared in this work, after a work of documentary sources that seek to recover local history from the perspective of its actors. This first approximation enables new readings of social processes, seeks to make the understanding of phenomena more complex, from a position that understands that they are contradictory and particular according to each socio-historical context. In this particular case, the interest is to recover the history of the Santa Fe School of Social Service, to approach the experiences of the first graduates who were building their own paths, questioning from their actions the mandates and stereotypes established in the epoch.
Keywords: Feminization; Social Work; Santa Fe; Findings; Professionalization